2014
DOI: 10.7205/milmed-d-13-00241
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking Behaviors and Impulsivity Among Veterans With and Without PTSD and Mild TBI

Abstract: Military personnel commonly experience post-traumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI), both of which are associated with premature mortality. The present study examined two factors that may play a role in premature mortality--impulsivity and risk-taking behaviors--in a sample of 234 veterans screening positive for PTSD, mTBI, PTSD + mTBI, and controls. Analyses of variance demonstrated that veterans with PTSD, regardless of mTBI status, reported engaging in more frequent risky beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 50 publications
5
76
0
Order By: Relevance
“…It is well-known that stress can increase impulsive behaviors such as drug abuse [31]–[34], risk taking behavior [35]–[38], and food intake [39]. In fact, enhanced formation of fearful memories and increased impulsivity (including risk taking behaviors, drug abuse, and emotional outburst) are both commonly observed in veterans repeatedly exposed to stressful environments [37]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that stress can increase impulsive behaviors such as drug abuse [31]–[34], risk taking behavior [35]–[38], and food intake [39]. In fact, enhanced formation of fearful memories and increased impulsivity (including risk taking behaviors, drug abuse, and emotional outburst) are both commonly observed in veterans repeatedly exposed to stressful environments [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Examples include substance use (James et al, 2014), risky sexual behaviors (Weiss et al, 2014), and deliberate self-harm (Weiss et al, 2015a). Indeed, a study on Veterans receiving treatment for PTSD indicated that a significant number of deaths were related to substance use, suicide, and homicide (Drescher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Depue and colleagues report that veterans with co-occurring mTBI and PTSD have reduced anterior amygdala volume relative to controls and that this volume reduction was associated with poor inhibitory control and increased self-reported impulsivity [29]. However, one study demonstrated among veterans with PTSD, mTBI, or cooccurring mTBI and PTSD, those with PTSD self-reported engaging in risky and impulsive behaviors regardless of mTBI diagnosis [30]. Interestingly, no studies to date have examined the cognitive domain of impulsivity using delayed or probability discounting procedures.…”
Section: Tbi-induced Cognitive Dysfunctionmentioning
confidence: 99%